Methods of teaching physics for non-physical bachelors by the method of "working in small groups" - Seytimbetova, Gulbadan (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
At present, modern teaching methods are widely used in the educational process. The use of modern teaching methods leads to high efficiency in the teaching process. When choosing teaching methods, it is advisable to choose based on the didactic function of each lesson